BACULOGYPSINA SULAIMANENSIS N. SP. (CALCARINIDAE) FROM THE PRIABONIAN OF SULAIMAN RANGE, PAKISTAN: A POSSIBLE ANCESTOR FOR THE RECENT BACULOGYPSINA SPHAERULATA - Ozcan, Ercan; Hohenegger, Johann; Yucel, Ali Osman; Kaygili, Sibel; Ali, Nowrad; Hanif, Muhammad (Cushman Foundation Foraminiferal Research, 2019)
Priabonian Pellatispira-beds' of the Drazinda Formation in Sulaiman Range, Pakistan, contain rare calcarinids displaying similar morphological traits known from Pliocene- Recent Baculogypsina (Sacco, 1893). These specimens possess a biconvex-lenticular test with 5-8 spines characterized by anastomosing canals. The small, poorly observed protoconch is followed by a series of low trochospiral chambers, which are followed by a cyclical arrangement of chambers, producing lateral chamberlets on both test sides. The lateral sides of the test are pierced by piles of almost uniform size. Spines arise from the initial spiral part and enlarge with growth. The shape, number, and size of lateral chambers are characteristic of the genus Baculogypsina, which extends the range of this genus into the late Eocene. We have assigned these previously undescribed specimens as Baculogypsina sulaimanensis n. sp. Occurring sporadically, the new taxon is associated with Heterostegina indusensis, Silvestriella tetraedra, Pellatispira madaraszi, Assilina ex. gr . alpina, and reticulate Nummulites.
Keywords: Larger Foraminifera; Benthic Foraminifera; Ryukyu Islands; Sesoko Island; Indus Basin; Orthophragminids; Tethys